Pedagogical documentation in early years practice : seeing through multiple perspectives - Fleet, Alma; Patterson, Catherine; Robertson, Janet (London : SAGE, 2017)
This text draws on the projects and experiences of senior researchers from nations including Australia, Canada, Sweden, Singapore, the UK and the USA to highlight multiple approaches to pedagogical documentation.
Part 1. Setting the stage -- The landscape of pedagogical documentation -- Pedagogical documentation and pedagogical choices -- Developing pedagogical. documentation within the EYFS curriculum framework -- Commentary 1: living with a growing idea -- Part 2. Languages of representation -- The worlds of the very young: seeing the everyday in small pieces -- Making learning visible in dance and other creative arts -- Using video in pedagogical documentation: interpretive and poetic possibilities -- Commentary 2: opening doors and windows -- Part 3. Embracing possibilities of change -- Collaborative decision-making within pedagogical documentation -- Pedagogic documentation and student learning -- Making the outdoors visible in pedagogical documentation -- Diving into the unknown: the experience of pedagogical documentation at Mia Mia -- Commentary 3: posing big(ger) ideas and questions -- Part 4. The wider view -- Knowledge and practice of pedagogic documentation: professional development for educators -- The potential of pedagogical documentation for leadership enactment -- Weavings, walks and wonderings: stories of the liveliness of pedagogical narrations -- Commentary 4: situating pedagogical documentation in a democratic context -- Pedagogical documentation: where to from here?
Includes bibliographical references and index.
Keywords: Early childhood education; Critical pedagogy; Observation (Educational method)